Spin coated YSZ thin films on silicon substrate - Palisoc, Shirley Tiong (Animo Repository, 2012)
Yttria Stabilized Zirconia (YSZ) thin films (<10 μm) were fabricated by spin coating technique on silicon (Si). Parameters such as concentration ratio of YSZ powder to solvent were varied accordingly. The effects of these variations were investigated and discussed. Using X-ray Diffraction and Raman Spectroscopy, the crystal structure of the samples were determined. The 8-YSZ thin films have cubic fluorite structure. The Xray diffraction patterns were in agree